Constructions of legitimacy: the Charles Taylor trial - Glasius, Marlies (International journal of transitional justice, 2012)
This article examines the discourses of the prosecution and the defence in the case of Charles Taylor before the Special Court for Sierra Leone. It contributes to current debates about the legitimacy and utility of international criminal justice, which have tended to neglect the examination of actual trials, and particularly the role of the defence. We draw on the legal doctrine of ‘expressivism’ to theorize the connection between normative legitimacy, actual support and the utility of international criminal justice as dynamic and partly determined in court. We conclude that the Taylor trial demonstrates three interrelated obstacles to the fulfilment of the expressivist promise: that a tension between criminal proceedings against a single person and truth telling about mass violence necessarily exists; that discourses do not appeal to all audiences equally, and that those which appeal to western audiences are likely to be privileged; and that these weaknesses will usually be exposed and exploited by the defence, weakening the legitimacy of case and court. In order to develop expressivism as an empirical theory, the elements of the actors, the audiences and the stage in the posited ‘courtroom drama’ require further research.